An Adolescent Male Patient of SLE Presenting With Early Lupus Nephritis, Rheumatic Heart Disease and Iatrogenic Cushing Syndrome - Dr. Radheshyam,Malviya, Dr. Ankit Rana, Dr. Bushra Khanam, Dr. Ajay Kumar Singh,Dr. Nisha Kalkal (International Journal of Innovative Research in Medical Science, 2016)
Systemic lupus erythematosus (SLE) is a multisystem autoimmune disorder. SLE is mimicked by other systemic disorders. Lupus nephritis is one of serious complications of SLE and is predictor of poor prognosis. Autoimmunity plays an important role in pathogenesis of SLE. We present herewith a rare case of young male who had presented with anasarca, palpitations, breathlessness, hypertension, proteinuria, with deranged renal function test, and was diagnosed as lupus nephritis on renal biopsy. The patient also had crossed renal ectopia, which makes this case very rare and one of its own kind in the whole world as yet. In addition, he also had a serious proliferative form of glomerular damage (ISN3 and ISN 4).